Accounting Treatment Evaluation of Fixed Assets under PSAP No.7 at Ministry of Food Crops and Horticulture - Galih Ramadhan Adinegara; Rina Tjandrakirana; Eka Meirawati (Journal of Social Science, 2023)
Fixed Assets has an important role to maximize the role of recording of recognition of fixed assets arising from transactions financed by the Regional Government. Under these circumstances decision-makers will urgently need information tools regarding fixed assets. This study aims to analyze the accounting treatment of fixed assets according to Financial Statements of Public Number 7 in the Department of Agriculture of Food Crops and Horticulture of South Sumatra Province. From the results of research the authors can conclude that the Department of Agriculture Food Crops and Horticulture of South Sumatra Province in carrying out its accounting activities whether already guided by Financial Statements of Public Number 7 About Fixed Assets.